Knowledge of the nursing team regarding transgender patients (Research, Society and Development, 2021)
Objective: To analyze the national and international scientific production on the level of knowledge of the nursing team regarding trans patients. Method: Integrative literature review in the Virtual Health Library (BVS) and Public Medline (PubMed) databases, using the intersections of the descriptors: Nursing care, Sexual and gender minorities, Transgender people, and their language counterparts English Nursing Care, Sexual and Gender Minorities and Trangender persons. In both languages these terms were combined using the Boolean operator and. An instrument was developed to collect information, consisting of the following items: title, journal, authors/year of publication and conclusion. Results: 11 studies were included, published between 2016-2020, later divided into two categories. Final considerations: it is evident the need for challenges to be overcome regarding the health care of the transgender community.